2009
DOI: 10.1007/s00436-009-1538-2
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo efficacies of ivermectin and cypermethrin against the cattle tick Hyalomma anatolicum anatolicum (Acari: Ixodidae)

Abstract: This study investigated the comparative efficacy of ivermectin and cypermethrin pour-on, for the treatment of Hyalomma anatolicum (a.) anatolicum infestations in bovines. For examining acaricidal efficacy, 480 ticks were exposed in vitro to graded doses of both the acaricides and in vivo efficacy was examined in 360 tick-infested bovines treated at the recommended doses of ivermectin (IVM) and cypermethrin (CYM) pour-on. The comparative quantitative assessment of tick burden was done on days 0, 5, 10, 15, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 35 publications
(44 reference statements)
2
25
2
Order By: Relevance
“…Only single species of tick Hylomma anatolicum was identified from the examined livestock of the area. The identified species of tick was also reported by (Sajid et al, 2009;Atif et al, 2012;Biu et al, 2012;Monfared et al, 2013;Mustafa et al, 2014) from other areas. Results of the present study are somewhat similar or different to the studies carried out earlier in other part of the globe (Irshad et al, 2010;Sajid et al, 2011;Ahmed et al, 2012;Monfared et al, 2013;Iqbal et al, 2013;Tasawar et al, 2014;Hassan and Al-Zubaidi, 2014;Mustafa et al, 2014).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Only single species of tick Hylomma anatolicum was identified from the examined livestock of the area. The identified species of tick was also reported by (Sajid et al, 2009;Atif et al, 2012;Biu et al, 2012;Monfared et al, 2013;Mustafa et al, 2014) from other areas. Results of the present study are somewhat similar or different to the studies carried out earlier in other part of the globe (Irshad et al, 2010;Sajid et al, 2011;Ahmed et al, 2012;Monfared et al, 2013;Iqbal et al, 2013;Tasawar et al, 2014;Hassan and Al-Zubaidi, 2014;Mustafa et al, 2014).…”
Section: Discussionsupporting
confidence: 77%
“…This could be due to the less attention has been paid by owner towards male in the investigated area and on the other hand hormonal effect mainly, androgen and oestrogen which had inhibitory and stimulatory effect on immune response due to which male animals are more prone to ticks then females (Bilbo and Nelson, 2001). Soft and pliable skin of young animal facilitates tick and prolongs duration of attachment (Sajid et al, 2009;Kabir et al, 2011). In male animals higher prevalence was also reported by (Tasawar et al, 2014).…”
Section: Ne Usmentioning
confidence: 99%
“…(Yang et al, 1993;Anbalagan et al, 2014), Prevalence of these species of ticks has already been reported in wide range of farm animals from the hilly and plain areas of Malaysia (Mariana et al, 2008). The results of present study indicate a relatively higher prevalence of ticks in the livestock populations of the plain and hilly areas of Pakistan as compared to earlier studies conducted in other parts of the country in which the prevalence ranged from 14% to 54.76% (Iqbal et al, 1971;Sajid et al, 2007Sajid et al, , 2008Ramzan et al, 2008;Sajid et al, 2009;Irshad et al, 2010;Sajid et al, 2011;Atif et al, 2012;Iqbal et al, 2013). The key factors which favour the growth and development of ticks in particular region are: temperature, humidity, rainfall (Greenfield et al, 2011), vegetation (Gray, 2002, host availability, season, habitat (Teel et al, 1996), altitude (Jouda et al, 2004;Burri et al, 2007;Cadenas et al, 2007), breed, age, sex, stage of lactation, gestation period, nutritional status of the animal (Swai et al, 2005;Alonso et al, 2007;Yacob et al, 2008), body condition (Rony et al, 2010), method of application of acaricides (Bianchi et al, 2003) and husbandry practices (Sajid et al, 2011).…”
Section: Discussioncontrasting
confidence: 44%
“…Tick distribution was found highest (P<0.05) in the Mansehra district followed by the Haripur, Batagram, Shangala, Kohistan, Diamer, Gilgit and Astor districts. Host age and sex (1) is much higher in the developing countries of Asia (Siddiqi and Jan, 1986;Khan et al, 1993;Sajid et al, 2007Sajid et al, , 2008Sajid et al, , 2009Sajid et al, , 2011Yi-Lun et al, 2011;Iqbal et al, 2013;Ali et al, 2013;Sultana et al, 2015) and Africa (Walker and Koney, 1999;Walker, 2003), where control measures are infrequently applied, than in Australia (Springell, 1974;Kamau, 2011), Europe (Papadopoulos et al, 1996;Hostis and Seegers, 2002) and the Americas (Guimaraes et al, 2001;Lohmeyer et al, 2011). Extensive research studies have been conducted on the prevalence of the tick fauna and associated risk factors in various districts of Pakistan.…”
Section: Discussionmentioning
confidence: 99%
“…Higher prevalence of T. annulata and A. marginale were reported in female animals (Durrani, 2008). Higher prevalence in female population was due to hormonal disturbances due to its use in milk production, draught power and breeding system which pose it to weakened immune system (Kamani et al, 2010;Sajid et al, 2009;Kabir et al, 2011).…”
Section: Sexmentioning
confidence: 99%